Inovasi Hilirisasi Produksi Ikan Nila di Desa Kanjilo sebagai Penggerak Ekonomi Lokal di Kabupaten Gowa - Achmad Anzhari Hasanuddin; Yohannis Yohannis; Faidah Azuz; Lukman Lukman; Wirjon Wirjon; Aldio Mukhlas Rizky; Iwan Perwira (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
This Community Service Programme addresses the theme of Empowering Beginner Communities (EBC), primarily focusing on the implementation of an initiative titled “Innovative Downstream Production of Nile Tilapia in Kanjilo Village as a Driver of Local Economy in Gowa Regency.” The objective of this programme is to enhance the capacity, skills, and productivity of Nile tilapia farmers through the adoption of more modern, efficient, and innovative technologies. Currently, the practices of tilapia farming in Kanjilo Village are largely reliant on traditional methods, which prove to be less effective. This results in suboptimal harvests, relatively high production costs, and low operational efficiency, thereby restricting the profits available to the community. To tackle these challenges, the programme introduces several cutting-edge aquaculture technologies. Firstly, the use of round tarpaulin ponds offers more efficient land utilisation, ease of management, and a high success rate. Secondly, the implementation of a biofloc system helps maintain water quality while accelerating fish growth. Thirdly, the application of nano-oxygen technology enhances dissolved oxygen levels, promoting healthier, stronger, and more productive fish. Through this combination of technologies, it is anticipated that the aquaculture system can be significantly improved, leading to quicker harvests, reduced operational costs, and increased income for fish farmers. In addition to the technical aspects of production, the programme also includes training in digital marketing strategies. This training aims to broaden the marketing reach of Nile tilapia products via online platforms, targeting consumers in Eastern Indonesia, a region with substantial potential yet to be fully tapped. By leveraging digital media, entrepreneurs can access a wider market, enhance product value, build local brands, and strengthen distribution networks. Consequently, this programme is expected to foster sustainable economic transformation in Kanjilo Village.